A comparison between conflict of interest in Western and Islamic literatures in the realm of medicine. - Mojtaba Parsa; Kiarash Aramesh; Bagher Larijani (Journal of Medical Ethics and History of Medicine, 2015)
In Western literatures, "conflict" is a general term that refers to discord between two or more entities. In Islamic jurisprudence, however, in addition to the term "conflict" (Taāruz), there is another term which is called tazāhum. The two terms, however, have different definitions. Conflict between two concepts, for instance, indicates that one is right and the other is wrong, while tazāhum does not necessarily have to be between right and wrong, and may appear between two equally right concepts. Moreover, conflict exists on a legislative level, while tazāhum is a matter of obedience and adherence, meaning that in practice, both sides cannot continue to coexist. Conflict of interest is a known term in Western literatures, and according to D.F. Thompson, it refers to a situation where professional judgment regarding a primary interest is improperly and unjustifiably influenced by a secondary interest. Taking into account Thompson's definition and the distinction between "conflict" (Taāruz) and "tazāhum", the English term "conflict of interest" translates to "tazāhum of interest" in Islamic jurisprudence as it refers to a person's action without reflecting right or wrong, and simply concerns priority of one interest over another. The resolution to tazāhum in Islamic jurisprudence lies in two principles: the principle of significance and the principle of choice. For instance, in case of conflict (the Western term) or tazāhum (the Islamic term) between the interests of patient and physician, the patient's interest should be the main concern based on the principle of significance. Although Western literatures propose methods such as disclosure or prohibition in order to resolve conflict of interest, the foundation for these solutions seems to have been the principle of significance.